Optimal decay rates for the acoustic wave motions with boundary memory damping - BENOMAR, Khalida; BENAISSA, Abbes (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
A linear wave equation with acoustic boundary conditions (ABC) on a portion of the boundary and Dirichlet conditions on the rest of the boundary is considered. The (ABC) contain a memory damping with respect to the normal displacement of the boundary point. In this paper, we establish polynomial energy decay rates for the wave equation by using resolvent estimates. Mathematics Subject Classification (2010): 93D15, 35B40, 47D03, 74D05.